Physiological basis of nano-silica deposition-related improvement in aluminum tolerance in pea (Pisum sativum) - Feng, Yingming; Zheng, Yuxin; Nong, Wei; Chen, Xingyun; Wang, Zeyan; Zeng, Peng; Li, Xuewen; Sergey, Shabala; Shi, Lei; Yu, Min (Frontiers in Plant Science, 2025)
Aluminum(Al) toxicity is a major constraint affecting crop growth in acidic soils across the globe. Excessive Al levels in such soils not only negatively affect crop growth but also have significant implications for human health. This study aimed to explore the feasibility of increasing tolerance to Al stress by creating biomineralization structures in plant roots by nano-silica, and to explore the physiological basis silicon-mediated alleviation of Al toxicity in plants. The polyethylenimine was used to induce nano-silica to form biomineralization structures on the surface of root tip and root border cells in pea (Pisum sativum) plants. The results showed that under Al stress conditions, the deposition of nano-silica on the cell wall of pea root border cells induced by polyethyleneimine effectively increased cell viability and reduced reactive oxygen species(ROS) production by 44%, thus slowing down the programmed cell death. Such deposition also resulted in more Al ions(Al3+) absorbed by the surface of the root tip, thus preventing Al3+ from entering the root tip and alleviating the toxic effects of Al on cell metabolism. It is concluded that polyethylenimine- induced nano-silica deposition on the cell wall endows pea root cells with Al tolerance, thus enhancing crop growth and reducing toxic Al load, contributing to food safety and human health.